Presumed incompetent II : race, class, power, and resistance of women in academia - Niemann, Yolanda Flores; Gutiérrez y Muhs, Gabriella; Gonzalez, Carmen G., 1962- (Utah State University Press, an imprint of University Press of Colorado, 2020)
"Women of color in academia are suffering, but they are also overcoming obstacles in inspiring ways. Presumed Incompetent II comes when women of color in America are facing new threats and their ability to survive in academia as the country grapples with the rhetorics of white supremacy"--